2022
DOI: 10.3390/su14031110
|View full text |Cite
|
Sign up to set email alerts
|

Optically Modulated Passive Broadband Daytime Radiative Cooling Materials Can Cool Cities in Summer and Heat Cities in Winter

Abstract: Broadband passive daytime radiative cooling (PDRC) materials exhibit sub-ambient surface temperatures and contribute highly to mitigating extreme urban heat during the warm period. However, their application may cause undesired overcooling problems in winter. This study aims to assess, on a city scale, different solutions to overcome the winter overcooling penalty derived from using PDRC materials. Furthermore, a mesoscale urban modeling system assesses the potential of the optical modulation of reflectance (ρ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…The recently developed super cool or daytime radiative cooling materials present a very high solar re ectance value combined with high emittance at the atmospheric window, while they have not yet been implemented to mitigate urban overheating. Mesoscale simulations for the city of Kolkata, India, have shown that super cool materials may contribute to decreasing the peak temperature of cities up to 4.5°C, imposing, however, a considerable heating penalty during the winter period [70]. Modulation of their optical properties, mainly re ectance and emittance, to reduce the strength of cooling during the cold period could minimize the problem [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…The recently developed super cool or daytime radiative cooling materials present a very high solar re ectance value combined with high emittance at the atmospheric window, while they have not yet been implemented to mitigate urban overheating. Mesoscale simulations for the city of Kolkata, India, have shown that super cool materials may contribute to decreasing the peak temperature of cities up to 4.5°C, imposing, however, a considerable heating penalty during the winter period [70]. Modulation of their optical properties, mainly re ectance and emittance, to reduce the strength of cooling during the cold period could minimize the problem [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…Optically modulated SCMs can be an efficient urban heat mitigation technology for use during the summer period without overcooling potential. Khan, Carlosena, et al (2022) concluded that the modulation of both solar reflectivity and infrared emissivity could increase the ambient temperature up to 0.4°C and 1.4°C during the day and night, respectively. Decreasing the burden of heat for urban environments has considerable benefits across society, including reduction of energy consumption, improvement in thermal comfort and health (Akbari et al, 2004;Ali-Toudert et al, 2005; H. Chen et al, 2009;Santamouris, 2020;Santamouris et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, CMs and SCMs are very reflective and can lead to an overcooling penalty at times. Recent research addressed this knowledge gap, calculating different solutions with optically modulated SCMs (Khan, Carlosena, et al., 2022). Optically modulated SCMs can be an efficient urban heat mitigation technology for use during the summer period without overcooling potential.…”
Section: Introductionmentioning
confidence: 99%
“…[ 32 ] In the years since, DRCs have gained tremendous popularity and are being investigated for a wide range of applications, including buildings, solar cells, the clothing industry, electricity generation, water harvesting, and UHI mitigation. [ 24,38 ]…”
Section: Introductionmentioning
confidence: 99%